FENOMENA PERILAKU STICKY COST PADA PERUSAHAAN MANUFAKTUR DI INDONESIA - Annida Afiffah; Yunika Murdayanti; Unggul Purwohedi (Universitas Kristen Krida Wacana, 2018)
The purpose of this research is to find indication of sticky cost behavior in behavior companies in Indonesia between 2014 until 2015 and to see whether the sticky cost will be more influential with the ewxistence of asset intensity and employee intensity. The indication of sticky cost can be seen from the a higher cost when sales volume is increasing compared to when sales volume is decreasing in the equal proporton. In this research selling, adminstration and general as a dependent variable. This research proves that there are indication sticky cost on manufacturing companies in Indonesia. The showing that, every 1% increase in net sales then the selling, administration and general costs increased by 0,328%. While when net sales decreased 1% then selling, administration an general costs decreased by 0,078%. The level of stickiness will be more attached when the asset intensity increased. While the employee intensity has no effect on the stickiness of the costs.Keywords: asset intensity, costs of selling administration and general, sticky cost, employee intensity, and net sales.